From structural violence to family violence: insights into perpetrators' experiences in French Polynesia today - Salaün, Marie (Family violence and social change in the Pacific Islands, 2023)
The empirical material on which this chapter is based comes from a survey carried out in 2019 as part of a research project on the relevance of specific penal care for the Indigenous populations in French Polynesia. This contribution focuses on the pervasiveness of multifaceted violence at the heart of prisoners’ experience, both as perpetrators and as victims. After looking at a few portraits depicting the diversity of individual situations, we return to a core feature of the offenders’ narratives: interpersonal violence. We argue that interpersonal violence requires an analysis in terms of structural violence, because violence as a process goes beyond individuals and their immediate social circles, to include contemporary French Polynesian society as a whole. We identify the way in which cycles of violent exchanges bring about specific local moral economies which is strongly out of step with the legal categories through which violence is comprehended, assessed, and punished by institutions.